Middle East’s circular economy expectations for the next ten years - Al Kufy, Dr.Firas (Open Science Journal, 2021)
This study provides an overview of waste management through circular economy in Middle East. Waste management has become a worldwide problem since humans are wasting resources as well as raw materials. This is the biggest problem faced by the humans on Earth that is getting attention of government representatives from all over the world. Recently, Middle East has also showed concerns regarding the amount of waste produced. Thus, several government representatives of Middle East have voiced their opinions and have taken an initiative to adopt this model. This article is based on the adoption of the model of circular economy in the countries of Middle East. This article explains the challenges that Middle East needs to be aware of for successful implementation of this model. <!--[if gte mso 9]> 1 1 1 1 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> MicrosoftInternetExplorer4 0 2 DocumentNotSpecified 7.8 磅 Normal 0 <![endif]--><!--[if gte mso 9]> <![endif]-->